Acoustic backscatter processing in GLOBE: an open-source software for echo sounder data analysis - Poncelet, C.; Saunier, A.; Gaillot, A.; Billant, G.; Berger, L. (Frontiers in Remote Sensing, 2025)
In order to meet the needs of a wide scientific community and take advantage of large echo sounder datasets collected at sea, Ifremer has developed GLOBE (GLobal Oceanographic Bathymetry Explorer), an open-source software program that integrates tools for bathymetry, water column, and now advanced seafloor backscatter processing. GLOBE follows standardized formats and methodologies, including the International Council For the Exploration of the Sea (ICES) SONAR-netCDF4 standard and the Geohab Backscatter Working Group (BSWG) recommendations, ensuring interoperability and reproducibility. GLOBE provides a comprehensive 3D georeferenced environment for visualizing and analyzing echo sounder data by merging datasets acquired on different platforms at various spatial and temporal scales. The applicability of GLOBE software for seafloor backscatter processing is presented and compared with that of existing tools. Its use is illustrated with a dataset of the multibeam water column and seafloor backscatter acquired by a research vessel and an underwater vehicle of the French Oceanographic Fleet (FOF) in the Tyrrhenian Sea.